Option Pricing-Based Bond Value Estimates and a Fundamental Components Approach to Account for Corporate Debt. - Barth, Mary E.; Landsman, Wayne R.; Rendleman, Richard J. (The Accounting Review, 1998)
This study provides evidence on the relevance and reliability of option pricing-based value estimates for bonds and their components, i.e., conversion, call, put and sinking fund features. Findings reveal component value estimates represent large fractions of bond par value, and a fundamental components approach to account for corporate debt results in key financial statement amounts significantly different from those presently recognized. Component value estimates and financial statement amounts vary significantly with component estimation order. Thus, bond value estimates potentially meet the FASE3's relevance criterion. However, estimate variation across component estimation orders and comparisons of estimates to available benchmarks indicate bond value estimates lack reliability.